The mutual perception between deputies and Spanish parliamentary journalists and its influence in political and media agendas - Rosa Berganza, María (2022)
This paper examines the relationship between parliamentary journalists and Spanish Members of Parliament. The study, based on surveys, is part of a European research in which Germany, Denmark and the United Kingdom have also participated. Among the key conclusions, it highlights the remarkable power of the media in politics and the sensationalism in political texts perceived by politicians. Concerning journalists, the majority felt that their professional work is driven by competition with other media and internal pressures, political and economic, coming from their own organization.